Pathogenic Mechanisms of Vaccine-Induced Immune Thrombotic Thrombocytopenia in People Receiving Anti-COVID-19 Adenoviral-Based Vaccines: A Proposal - Azzarone, Bruno; Veneziani, Irene; Moretta, Lorenzo; Maggi, Enrico (Frontiers in Immunology, 2021)
VITT is a rare, life-threatening syndrome characterized by thrombotic symptoms in combination with thrombocytopenia, that may touch individuals receiving the first administration of adenoviral non replicating vectors (AVV) anti Covid19 vaccines. VITT is characterized byhigh leves of serum IgG that binding to PF4/polyanion complexes trigger platelet activation. Therefore, identification of the fine pathophysiological mechanism by which vaccine components trigger platelet activation is mandatory. Herein, we propose a multistep mechanism involving both the AVV and the neo-synthetized Spike protein. The former can: i. promote the early production of high levels of IL-6, ii. spread rapidly into bloodstream, iii. interact with erytrocytes, platelets, mast cells and endothelia, iii. activated platelets and mast cells release PF4 and heparin. The pre-existence of natural antibodies binding PF4/ heparin complexes may amplify platelet activation and thrombotic events. Finally, neosynthesized Covid 19 Spike protein interacting with its ACE2 receptor on endothelia , platelets and leucocyte may trigger further thrombotic events unleashing the WITT syndrome.